Biomonitoring of Fresh Water of Loktak Lake, India - Sharat Singh, N.K.; Sudarshan, M. Sudarshan; Ch. Bino Devi, A. Chakraborty; Brojendro Singh, Th.; Rajmuhon Singh, N. (European Journal of Sustainable Development, 2014)
The fresh water Mollusca (Scientific name; Pila globosa) was collected from nine different stations of Loktak lake to investigate the elemental profile in the tissue of it as it can be used as biomonitor of the pollution of water. As the Gastropoda family is a feeder filter, it is very useful to examine the trace elements as well as toxic elements in the environment where it survives. The elements detected in the samples are Mg, Al, P, S, Cl, K, Ca, Mn, Fe, Cu, Zn, Se, Br, Rb, Sr and the elemental concentrations were compared with FAO limits to check their toxic levels. The elements detected so far are the time integral of their concentration so, that are several orders of magnitude above ambient water concentrations. The analysis of the elements was done with the help of energy dispersive X-ray fluorescence (EDXRF) for its quick and multi-elemental detection capability. Keywords: Pila globosa, Biomonitoring, Loktak lake, Trace elements, EDXRF